Academic Resilience in Mathematics Among Senior High School Students in Mindanao State University-Sulu - Talikan, Allen (Journal of Interdisciplinary Perspectives, 2024)
This study investigated the extent of academic resilience in mathematics among senior high school students at Mindanao State University-Sulu (MSU-Sulu). Descriptive-correlational research design was used to gather data from 120 respondents. The findings revealed the student-respondents are mostly females aged between 17-18 years old. There is an equal representation of grade levels, and most students' parents have a monthly income between P20,001.00 and P30,000.00. Additionally, the majority of parents are college graduates; 2) The student-respondents displayed a high positive attitude towards mathematics in most categories. However, they showed some ambiguity in the category of 'Struggle;' 3) The study revealed no significant differences based on gender, age, parents' monthly income, or educational attainment. However, grade level was found to be a notable factor, with grade 11 and grade 12 students exhibiting varying degrees of resilience. This suggests that students' perceptions of academic resilience in mathematics may develop as they progress through senior high school; 4) The findings also revealed that only the correlation between 'Value' and 'Growth' is statistically significant, although it is weak. The correlations between 'Value' and 'Struggle', and 'Struggle' and 'Growth' are not statistically significant. Consequently, the hypothesis stating that there is no significant correlation among the subcategories of academic resilience in mathematics is largely supported, except for the weak but significant correlation between 'Value' and 'Growth'. Based on these findings, the study recommends the following: 1) The University administrator should incorporate goals and strategies related to promoting academic resilience in mathematics into MSU's strategic planning initiatives and policies; 2) Faculty members of MSU-Sulu should adopt flexible instructional approaches that accommodate diverse learning styles and levels of mathematical proficiency among students; 3) They may also consider adopting student-centered pedagogical approaches that prioritize active learning, problem-solving, and collaboration in the classroom; and 4) Furthermore, future researchers in the field of mathematics education are encouraged to conduct similar studies to contribute to ongoing research on improving mathematical skills and academic resilience among the students. This will provide a foundation for continued advancements in the field.